Location strategies of dairy plants in India. (5th April 2010) - Sharma, Tejinder; Turka, Suresh Kumar; Bhutta, M. Khurrum S.; Natarajan, Vivek S.
Competing for a perennial supply of milk is a major factor influencing dairy plants, and theoretically, they must be positioned at an optimum distance between themselves in order to sustain their profitability. However, the location optimised on economic variables seldom corresponds with the actual location of a dairy plant as the final selection is an outcome of a complex set of variables, both objective and subjective in nature. This paper models the influence of various subjective and objective factors on location strategies of the dairy plants in India. Findings indicate that the demographic factors, represented as population density, employment and literacy emerge as the most significant influencers of the choice of a manufacturing location of small-, medium- and large-scale units. Among the subjective variables, the site specific and micro-factors, comprising of the regulatory framework, and the site-specific fixed costs score over the macro-factors while selecting a location.